Book Review: Entrepreneurship in a European Perspective: Concepts for the Creation and Growth of New Ventures by C.K. Volkmann, K.O. Tokarski and M. Gruenhagen. (29th November 2010) - Hytti, Ulla
Entrepreneurship in a European Perspective: Concepts for the Creation and Growth of New Ventures, by C.K. Volkmann, K.O. Tokarski and M. Gruenhagen. Wiesbaden, Gabler, 2010. 499pp. ISBN 978-3-8349-2067-6